Lectotypification of twelve names of the tribe Paullinieae (Sapindaceae) - Massing, Angelo Augustinho; Miotto, Sílvia Teresinha Sfoggia (Phytotaxa, 2020)
The Paullinieae tribe belongs to the Sapindaceae family and includes climbing plants, rarely erect, herbaceous or woody. The distribution is predominantly american, with some species found on other continents. In the review of the tribe, several nomenclatural problems were verified mainly in relation of the types identification. Therefore, in this work, twelve lectotypes are proposed: three species for the genus Paullinia, six for Serjania, two for Thinouia and one for Urvillea.